On dynamics of the system of two coupled nonlinear Schrödinger in R3. (12th August 2019) - Xia, Suxia; Xu, Chengbin
Abstract : In this paper, we give a new proof of the scattering and blow‐up theory of the two coupled nonlinear Schrödinger system via establishing the corresponding interaction Morawetz estimate and scattering criterion. The method of this paper simplifies the proof in Xu, and the result of the paper improves the result in Xu.